2012
DOI: 10.1111/j.1445-2197.2012.06114.x
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on survival from early breast cancer in clinical settings in Australia

Abstract: Background:  The study aim was to determine whether age is an independent risk factor for survival from early invasive breast cancer in contemporary Australian clinical settings. Methods:  The study included 31 493 breast cancers diagnosed in 1998–2005. Risk of death from breast cancer was compared by age, without and with adjustment for clinical risk factors, using Cox proportional hazard regression. Results:  Risk of breast cancer death was elevated for cancers of larger size, higher grade, positive nodal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
(39 reference statements)
4
6
0
Order By: Relevance
“…In the larger Slovenian cohort, these patients also had worse BCSS, compared to patients aged 40–70 years, but no worse than patients under 40. Similar trends have been reported in other countries (20).…”
Section: Discussionsupporting
confidence: 90%
“…In the larger Slovenian cohort, these patients also had worse BCSS, compared to patients aged 40–70 years, but no worse than patients under 40. Similar trends have been reported in other countries (20).…”
Section: Discussionsupporting
confidence: 90%
“…Balabram et al[20] performed a retrospective cohort study of 767 breast cancer patients in Brazil, the results of which indicated that women aged ≥70 and ≤35 exhibited shorter cancer-specific survival than patients aged between 36 and 69 years. Roder et al[21] analysed 493 breast cancer patients diagnosed from 1998–2005 in Australia and found that women under 40 years and over 70 years exhibited poorer overall survival than women between 40 and 69 years. Similarly, Brandt et al[12] studied 4,453 women who were diagnosed with breast cancer between 1961 and 1991 at a single institution in Sweden and were followed up for 10 years regarding breast cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of various factors with rate of survival after BC diagnosis has been evaluated and shown in different studies. For instance, Roder et al, (2012) showed that tumor size, stage of tumor, involvement of lymph nodes, estrogen receptor (ER) status, vascular status and being diffused correlate with survival rate after being diagnosed with BC. Dong et al, (2014) added menopausal status, and metastasis to armpit lymph nodes and the adjacent region to the factors correlating with survival after BC development (Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%